Effect of collagen crosslinkers on sodium hypochlorite treated dentin bond strength: a systematic review and meta-analysis - Zhou, Weiqing; Feng, Shuting; Chu, Xiaojun; Xu, Shuaimei; Zeng, Xiongqun (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe bond strength (BS) between composite resin and dentin is a crucial factor determining the long-term success of restorations. Sodium hypochlorite (NaOCl), a frequently used root canal irrigating agent, has been demonstrated to notably influence the properties of dentin, thereby affecting the BS. Moreover, the application of collagen crosslinkers has become a potential approach to improve the stability of the resin-dentin bond. Nevertheless, the effect of collagen crosslinkers on the bond strength (BS) between sodium hypochlorite (NaOCl) treated dentin and composite resin remains a topic of contention, and there is a lack of in-depth understanding in the existing literature. The purpose of this systematic review and meta-analysis was to analyze the current literature on the effect of collagen crosslinkers on the BS between sodium hypochlorite treated dentin and composite resin.MethodsDatabases including PubMed, EMBASE, Cochrane library, Scopus, Web of Science and SinoMed were searched. In vitro studies reported the effect of crosslinking agents on NaOCl-treated dentin BS were included. The reference lists of studies included via databases were manually searched for more studies that fulfilled the inclusion criteria. The initial search yielded 1,538 studies, and subsequent screening resulted in the inclusion of 14 studies. Most of studies (78.6%, 11/14) were categorized as having a “low” risk of bias. The studies included in the meta-analysis employed a range of cross-linking agents, including ethylenediaminetetraacetic acid (EDTA), phytic acid (IP6), proanthocyanidin (PA), rosmarinic acid (RA) and sodium ascorbate (SA). Subgroup comparisons were performed according to NaOCl exposure duration. Studies treated with different concentration of NaOCl were analyzed separately.ResultsFor dentin exposed less than 1 min or NaOCl at lower concentration, significant positive effect cannot be observed when using collagen crosslinkers. For dentin exposed more than 1 min in NaOCl at concentrations greater than 2.5%, EDTA, PA and SA were observed to significantly improve the BS. RA is proved effective in improving the BS of dentin exposed to high concentrations NaOCl within a shorter duration. Current evidence is insufficient to conclude that IP6 has a positive effect in NaOCl-treated dentin bonding performance.ConclusionThe effect of collagen crosslinkers on the BS of NaOCl treated dentin was influenced by the concentration of NaOCl and the duration of exposure.